2010
DOI: 10.1186/1477-7525-8-69
|View full text |Cite
|
Sign up to set email alerts
|

A 'short walk' is longer before radiotherapy than afterwards: a qualitative study questioning the baseline and follow-up design

Abstract: BackgroundNumerous studies have indirectly demonstrated changes in the content of respondents' QoL appraisal process over time by revealing response-shift effects. This is the first known study to qualitatively examine the assumption of consistency in the content of the cognitive processes underlying QoL appraisal over time. Specific objectives are to examine whether the content of each distinct cognitive process underlying QoL appraisal is (dis)similar over time and whether patterns of (dis)similarity can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 32 publications
0
22
1
2
Order By: Relevance
“…In fact, for some of the PROMIS measures, the general population mean overlapped with the categories for mild symptom levels [27,28]. This could indicate a response shift phenomenon [29], resulting in an underestimation of the true difference between cancer patients and the general population but may also reflect the high percentage of individuals suffering from (chronic) diseases in the general population. In the normative sample for the EORTC CAT Core [9], for example, 61.0% of the participants from the general population reported at least one health condition, with chronic pain (23%), arthritis (13%), and diabetes (10%) being most common.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, for some of the PROMIS measures, the general population mean overlapped with the categories for mild symptom levels [27,28]. This could indicate a response shift phenomenon [29], resulting in an underestimation of the true difference between cancer patients and the general population but may also reflect the high percentage of individuals suffering from (chronic) diseases in the general population. In the normative sample for the EORTC CAT Core [9], for example, 61.0% of the participants from the general population reported at least one health condition, with chronic pain (23%), arthritis (13%), and diabetes (10%) being most common.…”
Section: Discussionmentioning
confidence: 98%
“…For example, HIV/AIDS patients who reported better mental health than would be expected based on overt health status used appraisal strategies such as avoiding to think about things that are disappointing, worrisome, or difficult (Bobinski and Lipinski, 2009). The cognitive processes underlying patient response to patientreported outcome measures have also been found to change over time in cancer patients, and to be affected by treatment side-effects (Taminiau-Bloem et al, 2010). These findings suggest that QOL appraisal processes are relevant to resilience and adaptability.…”
Section: Introductionmentioning
confidence: 93%
“…Fluctuation over time is found in the work of Taminiau-Bloem et al who reported major changings in answering from baseline to follow up, in a sample of 50 cancer patients in aspects underlying OQL appraisal of e.g. taking a short walk, pain, fatigue, worry and overall quality of life [13]. Their finding calls for caution when giving attention to both quantitative and qualitative follow-up assessment.…”
Section: Introductionmentioning
confidence: 99%